Survival Rate Lemon Fish (Rachycentron canadum) Larvae in Lampung Marine Aquaculture Center - Tengku Rany Oktaviany; Suryadi Saputra; Irwan Effendi; Ummi Mardhiah Batubara (Tropical Marine Enviromental Sciences, 2022)
Cobia fish (Rachycentron canadum) is one of the marine carnivorous fish that is relatively new and has the potential to be cultuvited. This study aims to determine the effectiveness of larval rearing and nursery cobia fish found in the Center for Marine Aquaculture (BBPBL) Lampung. Held 20 January to 19 February 2021. The mature fish were mated in a 2x2x1 m concrete tank filled with 4,000 L of water. The eggs produced were harvested using an egg collector, counted and hatched in a 0.8x0.6x0.5 m aquarium. After hatching, the larvae were moved into nursery tanks with a density of 5-7 fish/L. Larvae were reared until they were 25 days old and fed naturally with Branchionus sp, Nannochloropsis sp, and artemia. The larvae were then counted, weighed, measured, graded and their growth analyzed. The results of this study showed that not all of these cobia eggs were fertilized by male cobia sperm at the time of spawning. Spawning was carried out on January 16, 2022. Total eggs was 648,000, total fertilized eggs was 480,000 and fertilization rate was 74.04 %. The results of the initial larval count were 75,000, 17,040 were harvested with a survival rate of 22.72%. Water quality (pH, DO, temperature, salinity, nitrite and ammonia) during the research was still normal.